ONLINE MUSIC PLAYER TO TEACH VOCABULARY - Nirna Nirmala; Marrieta Moddies Swara; Lastry Forsia (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Abstract It goes without saying that vocabulary mastery has a pivotal role in language learning. The more vocabulary the students acquire, the easier the students master the language skills. However, to acquire vocabulary is not an easy task for most students. To acquire vocabulary means that learners need to understand the aspects of vocabulary such as meaning, grammar, pronunciation, and spelling. However, the subjects of this study found it difficult to understand all the aspects. To overcome the problem, teacher needs to explore the use of teaching media. One of media that can be used in teaching vocabulary is song, but to make it more fun and practical, teacher can make use of online music player Joox, one of mostly used music player. This study explores the use of Joox to teach English vocabulary and describe students' responses to the teaching model. In general, students show good responses to the implementation of vocabulary learning using Joox. Therefore, it is recommended for teachers to use it as a medium in teaching vocabulary, and the students to use it for independent learning. Keywords: Joox, teaching media, teaching vocabulary